2021
DOI: 10.37856/bja.v96i1.4260
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crops and Their Relationship With the Qualitative and Quantitative Attributes of Soybeans

Abstract: The work aims to evaluate the effects of soil cover and soybean cultivars on the qualitative and quantitative attributes of soybeans. The experiment was conducted at Giruá, state of Rio Grande do Sul, Brazil. The experimental design was a randomized factorial block design, with two cover crops x seven soybean cultivars, disposed in three repetitions. Agricultural characteristics and nutritional attributes of soya were evaluated. The different coverings influenced the soybean performance for the main variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Follmann et al ( 2019) reported a broad-sense heritability (H²) of 0.93 for the 100-grain weight, while Barbosa et al (2021) found a narrow-sense heritability (h²) of 0.006, indicating a strong genetic influence. For the variables of crude fiber, mineral material, and palmitic acid, Bellinasso et al (2021) observed mean genotype heritability (h² g ) values of 0.26, 0.96, and 0.44, respectively. As for stearic fatty acid, oleic fatty acid, linoleic fatty acid, and linolenic fatty acid, this author noted broad-sense heritability (h² g ) values for total genotypic effects, with values of 0.82, 0.75, 0.78, and 0.53, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Follmann et al ( 2019) reported a broad-sense heritability (H²) of 0.93 for the 100-grain weight, while Barbosa et al (2021) found a narrow-sense heritability (h²) of 0.006, indicating a strong genetic influence. For the variables of crude fiber, mineral material, and palmitic acid, Bellinasso et al (2021) observed mean genotype heritability (h² g ) values of 0.26, 0.96, and 0.44, respectively. As for stearic fatty acid, oleic fatty acid, linoleic fatty acid, and linolenic fatty acid, this author noted broad-sense heritability (h² g ) values for total genotypic effects, with values of 0.82, 0.75, 0.78, and 0.53, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…According to Pipolo et al (2015), high temperatures during soybean grain filling contribute to the increase in oleic acid concentration, while lower temperatures increase the concentration of linoleic and linolenic acids. For industrial processing, the production of oils with greater oxidative stability is sought, that is, with higher oleic acid contents, and lower linoleic and linolenic acid contents, improving their usefulness at higher temperatures, for pharmaceutical purposes, cosmetics and industrial products such as biodiesel (Bellinasso et al, 2021;Figueiredo, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The MIII management demonstrated greater affinity with variables percentage of mineral material in the grain (MMG), percentage of stearic acid in the grain (AESTG) and number of branches (NB). The soybean grain is rich in minerals that are divided into macro and micronutrients, and the increase of these are of paramount importance in human and animal food (Bellinasso et al, 2021). For management MIV, the variables that stood out were: percentage of carbohydrates in the tissue (CHOT), which is positively influenced in the treatment, and neutral detergent fiber in the tissue (NDFT).…”
Section: Resultsmentioning
confidence: 99%